FEATURES OF IMPROVING THE SOCIAL CULTURAL COMPETENCIES OF FUTURE TRANSLATORS ON THE BASIS OF INTERDISCIPLINARY COMMUNICATION (Multidisciplinary Journal of Science and Technology, 2025)
Abstract: sociocultural competencies of future translators in the aspect of intercultural communication, structural components of communicative competencies, linguistic, sociolinguistic, discursive, sociocultural, strategic and social subcompetencies, communicative competence-linguistic (or linguistic) competence, knowledge of the language system, understanding of foreign language sentences and compilation, the studied foreign language provides information about skills and abilities that involve the possibility of speech and profanity communication with native speakers and mastering the information system about the language being studied.